Residential and school segregation as parameters of educational performance in Athens - Thomas Maloutas; Stavros Spyrellis; Andromachi Hadjiyanni; Antoinetta Capella; Despoina Valassi (Cybergeo, 2019)
The paper explores the relation of educational performance with social and urban inequalities in the Athens Metropolitan Area during the 2000s. It draws on discussions about education as a mechanism of social reproduction and on work about education inequalities in Greece, and in particular in Athens, where a socially stratified secondary education –compared to the rest of the country– leads to a rather open, but at the same time socially unequal higher education. We analyze how the performance of candidates in the Greek national admissions examination (Panelladikes Exetaseis) relates to the social position of candidates’ families, to the type of secondary schools they attended, to the social profile of candidates’ residential neighborhoods (tentatively) and to their demographic features (age and sex). The object is to illustrate and roughly quantify the function of social reproduction in this socially selective process of transition to higher education.